(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
In this analysis I consider the question of surrogacy contracts, adopting a critical perspective in order to assess whether it is possible to legitimize surrogacy as a contractual right. The current scenario needs regulation beyond prohibition. The normative claim regarding these contractual problems has not been properly addressed by current standard contracts. Here it is intended to consider how defensible is to support some of the main normative reasons aiming at justifying, in contemporary bioethical–legal debate, the prospect of a national system of pre–conception authorization of surrogacy agreements. I explore the various contractual problems of surrogacy contracts: the problem of unequal power of the contracting parties, the vulnerability of the contracting parties and the problem of autonomy of the surrogate mother. In conclusion, I agree that surrogacy contracts should be carefully regulated under an administrative–legal mechanisms for accomplishing their legal and social recognition.